2009
DOI: 10.1016/j.ijid.2009.02.005
|View full text |Cite
|
Sign up to set email alerts
|

A multi-level analysis of risk factors for Schistosoma japonicum infection in China

Abstract: The aim of this study was to explore the risk factors of schistosomiasis japonica in China, using a hierarchical multi-level model with individuals nested within villages. Methods: A cross-sectional survey of schistosomiasis japonica was conducted in 16 villages in the Chinese province of Hunan. A multi-level modeling technique (HLM version 6.04) was used to assess risk factors of schistosomiasis. The results from this multi-level model were compared with those from a conventional single-level logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 16 publications
7
21
0
Order By: Relevance
“…This is consistent with the findings from Sichuan province of China, which suggested that mean rainfall should be considered as the critical natural predictor for the prevalence of clonorchiasis [13]. Similarly, some published literature also indicated that rainfall were associated with schistosomiasis japonica infection in China [20,21], of which Xu XJ and his research team [22] proved that prevalence of schistosomiasis showed a significant linear regression relationship with annual rainfall. In Guangzhou, it is very common for rural households having a pond where fish are bred as a source of food.…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with the findings from Sichuan province of China, which suggested that mean rainfall should be considered as the critical natural predictor for the prevalence of clonorchiasis [13]. Similarly, some published literature also indicated that rainfall were associated with schistosomiasis japonica infection in China [20,21], of which Xu XJ and his research team [22] proved that prevalence of schistosomiasis showed a significant linear regression relationship with annual rainfall. In Guangzhou, it is very common for rural households having a pond where fish are bred as a source of food.…”
Section: Discussionsupporting
confidence: 85%
“…Small-scale, micro-epidemiological studies investigating risk factors for Schistosoma infection are often limited by their lack of data on individual-level cercarial exposure (for example, [51]). Although some studies have attempted to overcome this limitation by using proxy markers for exposure such as distance to an infective water body [52], [53], care should be taken because exposure to S. mansoni infection is a highly complex, multi-factorial process [54] and unreliable exposure estimates may bias results [45].…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk factors (61,119,166,223) and means of becoming infected (i.e., occupation [fishing and farming], domestic duties [washing], and social activities [swimming]) are likely similar in the areas of endemicity around both Poyang and Dongting Lakes, there are subtle differences in the patterns of transmission. The areas of endemicity in the Poyang Lake region have two distinct transmission seasons.…”
Section: Transmission Patternsmentioning
confidence: 99%